The critique and the consecration of Helena Kolody in the literary and intellectual field of Paraná - Schneider, Claércio Ivan [UNESP]; Boruch, Tiago (Universidade Estadual de Ponta Grossa (UEPG), 2018)
This article aims to understand, with methodological support by Pierre Bourdieu, the critique and the consecration of the poetess Helena Kolody and her creative project in the literary and intellectual paranaense field. We seek to inquire the author's intellectual position as well as analyze, from its poetic construction, the regional representations that Kolody reproduces around of the ideal immigrant figure - religious, laborious and modernized - influenced by the ideals of the Paranista Movement. For this to happen, we followed the way of criticism that consolidated the name of the poetess as “authorized” interpreter of Paraná, as well as searching in the work the elements of identity, culture and of everyday Slavic which played an important role in the representation of Ukrainian immigrants. We seek to demonstrate that the consecration of poetess as spokesperson of Ukrainian culture in the Paraná is connect to regional themes and the use of a set of symbols, representations and memories that meet the official precepts which tell the saga of immigrants in the Paraná. Representation which excludes from the Paraná the ethnic and social diversity described already for a long time by a contemporary historiography.
A crítica e a consagração de Helena Kolody no campo literário e intelectual paranaense
Keywords: Consecration field; Helena Kolody; Paranismo; Ukrainian immigrants